The social wasp fauna of a riparian forest in southeastern Brazil (hymenoptera, vespidae) - Locher, G. A. [UNESP]; Togni, O. C. [UNESP]; Silveira, O. T.; Giannotti, E. [UNESP] (Universidade Estadual de Feira de Santana, 2014)
An inventory of social wasps was carried out on a monthly basis, from March 2010 to March 2011 in a section of riparian forest along the Passa-Cinco River in Ipeúna, São Paulo state, Brazil. Two active collecting methods (active collecting and point sampling using a liquid bait) and one passive method (baited PET bottle trap) were used. The results increased the data on the diversity of social wasps of the State and were used to compare richness, equitability and diversity obtained with several collecting methods which have been employed to social wasps. Thirty-one species belonging to eight genera were recorded; the most abundant were Agelaia vicina (de Saussure) and Agelaia pallipes (Olivier). Both species belong to the tribe Epiponini, which was dominant in the sample. Regarding sampling methods, the active collecting ones sampled the greatest richness value and the highest Shannon-Wiener diversity index and also presented the largest number of exclusive species. However, the other methods have also obtained exclusive species.
Keywords: Abundance; Active sampling; Attractive traps; Polistinae; Richness